Cross-cultural adaptation of the awareness and beliefs about cancer measure for Hispanics/Latinos living in the United States - Contreras, Jennifer; Wang, Chun; Castillo, Wendy Camelo; Caicedo, Juan; Guerrero Vázquez, Monica; Robalino, Tania; Hidalgo-Arroyo, Aida; Villalonga-Olives, Ester (Frontiers in Public Health, 2024)
The purpose of this study is to culturally adapt the Awareness and Beliefs about Cancer (ABC) measure for use in the Hispanic/Latino population living in the United States (US). In accordance with Patient Reported Outcomes-Consortium guidelines for cross-cultural adaptation of measures for content and linguistic validity, we conducted: two forward-translations, reconciliation, two backtranslations, revision and harmonization, six cognitive interviews, revision, external expert review, and final version. Taking a mixed-methods approach, we conducted cognitive interviews with 22 Hispanic/Latino community members as well as convened an expert panel of six clinicians, health professionals, and community representatives and involved them in the entire process. After crossculturally adapting the ABC measure, we assessed the psychometric properties of the instrument using item response theory analysis. Item parameters, discrimination and category thresholds, and standard errors were calculated. For each of the adapted subdomains, we used item information curves to report the graphical profile of item effectiveness. Twenty-two Hispanic/Latino community members were enrolled for cognitive interviews and 726 Hispanics/Latinos fluent in Spanish completed the measure to assess its psychometric properties. Cognitive interviews revealed opportunities to improve items. Key changes from the original measure were inclusion of gender inclusive language and inquiry of e-cigarette use on items related to smoking habits. Psychometric properties analyses revealed that the anticipated delay of seeking medical help, general cancer beliefs, and cancer screening beliefs and behaviors subdomains had some slope parameters that were < 1; this implies those items were not able to adequately discriminate the latent trait and had poor performance. The adapted ABC measure for US Hispanics/Latinos meets content and linguistic validity standards, with construct validity confirmed for the cancer symptom recognition and barriers to symptomatic presentation subdomains, but revisions are necessary for others, highlighting the need for ongoing refinement to ensure cultural appropriateness of instruments.